Posyandu Cadres’ Roles in Supporting Stunting-Free Village Initiatives: Peran Petugas Posyandu dalam Mendukung Inisiatif Desa Bebas Stunting - Hamri Oky; Ilmi Usrotin Choiriyah (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Stunting remains a critical public health concern in Indonesia, requiring community-based prevention at the village level. Specific Background: Posyandu cadres serve as frontline community actors who assist health workers in monitoring child growth and educating mothers. Knowledge Gap: Limited studies describe how cadres’ roles operate through behavioral, facility, and social support factors in village stunting prevention. Aims: This study examines the roles of toddler Posyandu cadres in Balongdowo Village using Lawrence Green’s predisposing, enabling, and reinforcing factors. Results: Findings show that cadres actively provide education through pregnant-mother classes and WhatsApp communication (predisposing), face limitations in facilities and infrastructure that require borrowing equipment and personal initiative (enabling), and receive strong support through training and collaboration with health professionals and nutritionists (reinforcing). However, participation barriers and limited cadre capacity due to age remain challenges. Novelty: The study integrates behavioral theory with real community health practices to explain how cadre roles function within village stunting prevention. Implications: Strengthening facilities, cadre regeneration, and sustained training are essential to support community-driven stunting prevention and village health services.